Usefulness of MMP-9/TIMP-1 ratio in estimation of lung cancer invasion and metastasis - Kopczyńska, Ewa; Dancewicz, Maciej; Kowalewski, Janusz; Makarewicz, Wojciech; Kardymowicz, Hanna; Tyrakowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2007)
Background: Matrix metalloproteinases (MMPs) are proteolytic enzymes involved in extracellular matrix degradation, and thus in tumour invasion and metastasis. In tissue MMPs occur in complexes with their inhibitors (TIMPs). Matrix metallo- proteinase-9 (MMP-9) belongs to gelatinases, that catalyze proteolysis of different types of collagen, mainly type IV. The specific inhibitor of MMP-9 is TIMP-1. The MMP-9/TIMP-1 expression ratio defines MMP9 activity in vivo. Metalloproteinase-9 plays a role in cancer progression. Its increased expression (concentration) has been found in various tumours, including lung cancer. Aim of study: The aim of this study was indirect estimation of effective MMP-9 activity in lung cancer patients, by serum MMP-9/TIMP-1 concentration ratio. Material and methods: The study group consisted of 49 patients with non-small-cell lung cancer (16 females and 33 males) ranging in age from 47 to 80 years (mean age 63 ± 8.2). Serum concentration of MMP9 and TIMP-1 was evaluated by ELISA. Results: MMP-9 serum concentration and MMP-9/TIMP-1 ratio were significantly higher in IIIB-IV stage than I-IIIA, whereas TIMP-1 concentration did not show increasing tendency with tumour stage. The correlation coefficient between MMP-9 and TIMP1 was 0.385 (p<0.01). Conclusions: In later stages of lung cancer the balance between MMP-9 and TIMP-1 is altered, and MMP-9 effective activity is increased.